2019
DOI: 10.1097/mao.0000000000002326
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Emotional Burden of the Epley Maneuver in the Elderly

Abstract: Objective: To analyze and compare experiences of anxiety and discomfort caused by the Epley maneuver and the willingness for a potential retreatment between younger (≤70 yr) and older (>70 yr) patients. Study Design: Prospective, observational cohort study. Setting: Tertiary referral center. Methods: Dutch adults, diagnosed with posterior canal benign paroxysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The vestibular function of elderly patients suffers from age-related decline 36 , 42 . In addition, elderly patients are more likely to develop anxiety, which has also been shown to promote occurrence of RD 5 , 42 . Cha et al found that brain atrophy was related to long-lasting dizziness after BPPV treatment and speculated that there may be a relationship between brain atrophy and otoneurologic diseases 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vestibular function of elderly patients suffers from age-related decline 36 , 42 . In addition, elderly patients are more likely to develop anxiety, which has also been shown to promote occurrence of RD 5 , 42 . Cha et al found that brain atrophy was related to long-lasting dizziness after BPPV treatment and speculated that there may be a relationship between brain atrophy and otoneurologic diseases 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Most BPPV patients do not think that it is a malignant due to its name, but it can have a serious impact on patients' daily activities. BPPV can have a huge impact on patient's quality of life, and is closely related to patients' anxiety and depression, due to an increased risk of falls 2 , 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…25,28,59 Maas et al reported that, specifically in older adults, nausea could indeed be a side effect of the Epley maneuver in the first days post-treatment. 62 Potential explanations for age differences in BPPV treatment success Despite the fact that BPPV is the most common vestibular disorder, it has a low recognition rate in primary health care, particularly in older adults. 4,8,63 Older adults report disequilibrium or imbalance as the clinical presentation of BPPV, without reporting vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…However, several side effects related to the standard mEpley have been reported, such as a falling sensation, anxiety, and discomfort [10]. According to a clinical practice guideline, minor side effects such as nausea or imbalance may be associated with the standard mEpley, and these side effects might lead patients to be hesitant to undergo repeated maneuvers and an extended treatment period [11]. From the clinician's standpoint, rotating the patient's head below the table while holding it in the air is strenuous and can fatigue the clinician's arms and back.…”
Section: Discussionmentioning
confidence: 99%